Transformações psíquicas da paternidade na viuvez: uma abordagem Junguiana - Torolho, Priscila da Rocha Diodato (2011)
This study investigates the psychic transformation that occurs in the process of widowhood for fathers. It focuses on how fathers comprehend the meaning of widowhood and how it can interfere with the individuation process in light of Analytical Psychology. Qualitative interviews were conducted with three widowed men between the ages of 30 to 56. In these interviews, the impact of widowhood on the relationship between the fathers and their children were examined; specifically how their lives changed since the death of their wives/mothers respectively. The mourning process influenced how these fathers function. The results suggest that the typical experience of these fathers is that they are living in extreme conditions, where they are solely responsible for their children. These widowers with children live in different states than other fathers whose wives have not died. These states develop in adverse conditions marked by the absence of a female figure. At the same time, they show potential and opportunities for reconnection with shadow contents that have been neglected and with the anima announcing new ways and possibilities in the individuation process. The understanding of how to be a father in widowhood can be seen as a situation of psychic vulnerability caused by loss, and transformation of the self-image caused by single parenthood. It is an unusual experience that allows the construction of their own ways of being themselves and with their children